Mentoring within the federal innovation platform System of Personalized Training in a Higher Education Establishment - A. I. Artyukhina; E. V. Shishkina; V. I. Chumakov; A. A. Rybin; V. A. Kuznetsova (Кардиоваскулярная терапия и профилактика)
Aim. The article is devoted to the analysis of personalized training through the lens of the mentoring system at a medical university.Material and methods. The study involved 211 full-time 1st-6th year students of the Volgograd State Medical University. A sociological survey was used in the form of a questionnaire.Results. The article reveals the role of mentoring within federal innovation platform System of Personalized Training in a Higher Education Establishment. The authors substantiate the need to introduce a mentoring model to optimize the educational process and unlock the potential of students, residents, and teachers. The article examines the conceptual foundations, goals and objectives of mentoring, as well as implementation arrangements within the federal innovation platform. Additionally, the mentoring model benefits presented, including improved academic performance, increased student motivation, professional skill development, and career counseling. It also emphasizes the importance of monitoring and evaluating the effectiveness of the mentoring model to ensure its continuous modernization.Conclusion. The article emphasizes that the introduction of a mentoring model in the federal innovation platform System of Personalized Training in a Higher Education Establishment is an important step to achieve the goals of personalized training. The authors recommend future research on the implementation and evaluation of mentoring models in different higher education contexts.